New perspectives on catecholaminergic regulation of executive circuits: evidence for independent modulation of prefrontal functions by midbrain dopaminergic and noradrenergic neurons - Chandler, Daniel J.; Waterhouse, Barry D.; Gao, Wen-Jun (Frontiers in Neural Circuits, 2014)
Cognitive functions associated with prefrontal cortex, such as working memory and attention, are strongly influenced by catecholamine (dopamine, DA and norepinephrine, NE) release. Midbrain dopaminergic neurons in the ventral tegmental area (VTA) and noradrenergic neurons in the locus coeruleus (LC) are major sources of DA and NE to the prefrontal cortex. It is traditionally believed that DA and NE neurons are homogeneous with highly divergent axons innervating multiple terminal fields and once released, DA and NE individually or complementarily modulate the prefrontal functions and other brain regions. However, recent studies indicate that both DA and NE neurons in the mammalian brain are heterogeneous with a great degree of diversity, including their developmental lineages, molecular phenotypes, projection targets, afferent inputs, synaptic connectivity, physiological properties, and behavioral functions. These diverse characteristics could potentially endow DA and NE neurons with distinct roles in executive function, and alterations in their responses to genetic and epigenetic risk factors during development may contribute to distinct phenotypic and functional changes in disease states. In this review of recent literature, we discuss how these advances in DA and NE neurons change our thinking of catecholamine influences in cognitive functions in the brain, especially functions related to prefrontal cortex. We review how the projection-target specific populations of neurons in these two systems execute their functions in both normal and abnormal conditions. Additionally, we explore what open questions remain and suggest where future research needs to move in order to provide perspective insight into the cause of neuropsychiatric disorders related to DA and NE systems.